Антология выдающихся достижений в науке и технике. Часть 3: Открытие и изучение строения атома вещества - Баранов, Михаил Иванович (НТУ "ХПИ", 2011)
Приведен краткий научно-исторический очерк из всемирной истории открытия строения атомов материи, имеющего фундаментальное значение для человечества при познании природы, развития науки и техники

A brief outline from the global history of study and discovery of atomic structure of matter, which is of fundamental significance for mankind in cognition of Nature, development of science and technology
An anthology of outstanding achievements in science and technology. Part 3: Discovery and study of atomic structure of matter
Keywords: основы мироздания; материя; природа; химические элементы; history; atom; structure of matter